Galectin-3 Determines Tumor Cell Adaptive Strategies in Stressed Tumor Microenvironments - Cardoso, Ana Carolina Ferreira; Andrade, Luciana Nogueira de Sousa; Bustos, Silvina Odete; Chammas, Roger (Frontiers in Oncology, 2016)
Galectin-3 is a member of the b-galactoside binding lectin family, whose expression is often dysregulated in cancers. While galectin-3 is usually an intracellular protein, found in the nucleus and in the cytoplasm; under certain conditions, galectin-3 can be secreted by an yet unknown mechanism. Under stressing conditions (hypoxia and nutrient deprivation, e.g.) galectin-3 is upregulated, through the activity of transcription factors such as HIF-1a and NF-kB. Here we review evidence that indicates a positive role for galectin-3 in MAPK family signal transduction, leading to cell proliferation and cell survival. Galectin-3 serves as a scaffold protein, which favors the spatial organization of signaling proteins as K-RAS. Upon secretion, extracellular galectin-3 interacts with a variety of cell surface glycoproteins, such as growth factor receptors, integrins, cadherins and members of the Notch family, among other glycoproteins, besides different extracellular matrix molecules. Through its ability to oligomerize, galectin-3 forms lectin lattices that act as scaffolds that sustain the spatial organization of signaling receptors on the cell surface, dictating its maintenance on the plasma membrane or their endocytosis. Galectin-3 induces tumor cell, endothelial cell and leukocyte migration, favoring either the exit of tumor cells from a stressed microenvironment or the entry of endothelial cells and leukocytes, such as monocyte/macrophages into the tumor organoid. Therefore, galectin-3 plays homeostatic roles in tumors, besides its effects in different elements of the immune system, as (i) it favors tumor cell adaptation for survival in stressed conditions; (ii) upon secretion, galectin-3 induces tumor cell detachment and migration; (iii) it attracts endothelial cells and monocytes/macrophages to the tumor mass, inducing both directly and indirectly the process of angiogenesis. These activities are potentially targetable and specific interventions may be designed to counteract the protumoral role of galectin-3.